1999
DOI: 10.1109/48.740153
|View full text |Cite
|
Sign up to set email alerts
|

A modeling study of acoustic propagation through moving shallow-water solitary wave packets

Abstract: Abstract-Propagation of 400-Hz sound through continentalshelf internal solitary wave packets is shown by numerical simulation to be strongly influenced by coupling of normal modes. Coupling in a packet is controlled by the mode coefficients at the point where sound enters the packet, the dimensions of the waves and packet, and the ambient depth structures of temperature and salinity. In the case of a moving packet, changes of phases of the incident modes with respect to each other dominate over the other facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 18 publications
(45 reference statements)
2
55
0
1
Order By: Relevance
“…The themocline of the background sound speed profile shown in Fig. 1(a) is perturbed by the waves, which will cause acoustic mode coupling (Duda and Preisig, 1999). Figure 5(b) presents the modal arrival pulses received on the array located 20 km away from a 55 m deep source.…”
Section: E Effects Of Nonlinear Internal Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The themocline of the background sound speed profile shown in Fig. 1(a) is perturbed by the waves, which will cause acoustic mode coupling (Duda and Preisig, 1999). Figure 5(b) presents the modal arrival pulses received on the array located 20 km away from a 55 m deep source.…”
Section: E Effects Of Nonlinear Internal Wavesmentioning
confidence: 99%
“…It can be observed that at the times when internal waves were present, the standard deviation of the 1.5 min localization record also increased. It is known that nonlinear internal waves can distort the coherent structure of the sound field due to mode coupling (Duda and Preisig, 1999) and 3-D sound propagation effects (Lynch et al, 2010). When there is a nonlinear internal wave group in the propagation path, the localization suffers from these propagation effects and the performance can be degraded.…”
Section: Environmental Effectsmentioning
confidence: 99%
“…Since only few significant (sometimes also called dominant) modes [4,38] carry most of the coupled energy within the SIA and smooth-shaped waves, uncoupling of the mode m back into mode n will result in almost total uncoupling of mode m if either of modes n or m is dominant.…”
Section: A Steep Horizontal Grazing Anglesmentioning
confidence: 99%
“…Nonlinear internal waves [4,38], giant bottom waves [23], or large surface swell waves [27] are good examples for this. For the case of internal waves, low frequency acoustic propagation has been traditionally divided into four regimes [39] depending on the horizontal grazing angle.…”
Section: Sharp Interface Approximationmentioning
confidence: 99%
“…For the case of sound propagating through (perpendicular to the wavefront of) an internal solitary wave (ISW), Preisig and Duda (1997) showed that the energy shifts between modes at the steep faces of the ISW's, occurs over ranges of tens of meters, and is driven by the relative phases (differences of phases of the complex modeamplitude coefficients) of the dominant modes. The coupling of energy between modes in the shallow water waveguide results in a temporally fluctuating gain or loss of acoustic energy received at ranges of 10's of km from the acoustic source, depending on the source depth and the amplitude and placement of the ISW in the waveguide (Duda and Preisig, 1999).…”
mentioning
confidence: 99%